Management of recurrent and persistent metastatic lymph nodes in well‐differentiated thyroid cancer: A multifactorial decision‐making guide for the thyroid cancer care collaborative. Issue 4 (3rd April 2014) - Urken, Mark L.; Milas, Mira; Randolph, Gregory W.; Tufano, Ralph; Bergman, Donald; Bernet, Victor; Brett, Elise M.; Brierley, James D.; Cobin, Rhoda; Doherty, Gerard; Klopper, Joshua; Lee, Stephanie; et al.
Abstract: Background: Well‐differentiated thyroid cancer (WDTC) recurs in up to 30% of patients. Guidelines from the American Thyroid Association (ATA) and the National Comprehensive Cancer Network (NCCN) provide valuable parameters for the management of recurrent disease, but fail to guide the clinician as to the multitude of factors that should be taken into account. The Thyroid Cancer Care Collaborative (TCCC) is a web‐based repository of a patient's clinical information. Ten clinical decision‐making modules (CDMMs) process this information and display individualized treatment recommendations. Methods: We conducted a review of the literature and analysis of the management of patients with recurrent/persistent WDTC. Results: Surgery remains the most common treatment in recurrent/persistent WDTC and can be performed with limited morbidity in experienced hands. However, careful observation may be the recommended course in select patients. Reoperation yields biochemical remission rates between 21% and 66%. There is a reported 1.2% incidence of permanent unexpected nerve paralysis and a 3.5% incidence of permanent hypoparathyroidism. External beam radiotherapy and percutaneous ethanol ablation have been reported as therapeutic alternatives. Radioactive iodine as a primary therapy has been reported previously for metastatic lymph nodes, but is currently advocated by the ATA as an adjuvant to surgery. Conclusion: The management of recurrent lymph nodes is a multifactorial decision and is best determined by a multidisciplinary team. The CDMMs allow for easy adoption of contemporary knowledge, making this information accessible to both patient and clinician. © 2014 Wiley Periodicals, Inc. Head Neck 37 : 605–614, 2015